Branching of annual apple seedlings of medium-sized varieties with the influence of agrotechnical methods - N. G. Krasova; E. Yu. Koroliov; A. M. Galasheva (Овощи России, 2020)
Relevance. The basis for obtaining a large crop volume and its high level of precocity is the use of Apple planting material that fully meets modern standards of intensive gardening. The main purpose of these studies was to study methods of branching stimulation and determine their effectiveness in obtaining branched apple seedlings at the age of one year. Material and methods. The use of non-root treatments and fertilizers as regulators and growth stimulators of apple seedlings does not lead to a significant increase in the number of side branches. Significant growth of the crown of annual seedlings occurs when using mechanical methods to stimulate the growth of side branches. The use of such an agrotechnical technique as a single plucking made it possible to obtain 1-2.6 side branches on different orts. When using this method, but with the simultaneous removal of 3-4 leaf plates, it increased the production of side branches by 1.6-3.7 pieces. One of the most unresponsive to the use of agricultural techniques was the variety "Svezhest". Results. It is effective to apply to annual apple seedlings agrotechnical methods of stimulation of lateral branching by plucking with simultaneous removal of leaf plates in the amount of three to four pieces. These measures must be carried out before reaching the height of the seedling from seventy to eighty centimeters. It should be noted that the use of plucking only, without removing the leaf plates, does not give such an effect.